2012
DOI: 10.1155/2012/962496
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Thickness of Middle Ear Mucosa Using MRI and CT Imaging versus Histopathology

Abstract: Objective. Otitis media (OM) is characterized by increased middle ear effusion and inflammation of middle ear tissue. In this study, we compared two radiographic methods of analyzing inflammation by measuring mucosal thickness (MT). Methods. 28 chinchillas were divided into three treatment groups consisting of a vehicle control group and two glucocorticoid groups. 6 underwent treatment by vehicle control, 10 were treated with ciprofloxacin 0.3%/dexamethasone 0.1% (DEX), and 10 received ciprofloxacin 0.2%/hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some studies have reported the MRI findings of temporal bone abnormalities [9][12]. On MR images, air and bone are black, and it is easy to distinguish air or bone from mucosal edema or hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the MRI findings of temporal bone abnormalities [9][12]. On MR images, air and bone are black, and it is easy to distinguish air or bone from mucosal edema or hemorrhage.…”
Section: Introductionmentioning
confidence: 99%